Recent Work on Moral Revolutions. (20th May 2022) - Klenk, Michael; O'Neill, Elizabeth; Arora, Chirag; Blunden, Charlie; Eriksen, Cecilie; Frank, Lily; Hopster, Jeroen
Abstract: In the last few decades, several philosophers have written on the topic of moral revolutions, distinguishing them from other kinds of society-level moral change. This article surveys recent accounts of moral revolutions in moral philosophy. Different authors use quite different criteria to pick out moral revolutions. Features treated as relevant include radicality, depth or fundamentality, pervasiveness, novelty and particular causes. We also characterize the factors that have been proposed to cause moral revolutions, including anomalies in existing moral codes, changing honour codes, art, economic conditions and individuals or groups. Finally, we discuss what accounts of moral revolutions have in common, how they differ and how moral revolutions are distinguished from other kinds of moral change, such as drift and reform.